Speleotourism potential and tourist experience in Resava cave - Antić, Aleksandar (Hotel and Tourism Management, 2018)
Resava Cave is a very old cave in Eastern Serbia, authentic and popular, with special geological and geomorphological features that are excellent representatives of the area’s geodiversity. Most of the speleotourism and geotourism potential of this geosite still remains unlocked. This paper provides an analysis of the tourist potential and tourist experience for speleotourism development of Resava Cave. The aim was to explore the speleotourism potential of Resava cave and to determine and compare tourist experience while visiting this cave. The research includes a a survey of tourists who visited Resava Cave during the month of May, 2018. Each respondent was asked a total of sixteen questions related to their social-demographic profile, the evaluation of certain speleotourist indicators and the tourists’ personal attitude to their experience in the cave. Results of the paper have shown that the tourism potential is very high and experiences are diverse, but some of them are more present than the others.